The scale logic of government debt for overall development and security: From the perspective of dual scale economy of explicit and implicit debt - Yunxiao Yuan; Xiaoyu Yang; Muhammad Umer (Economies, 2025)
Government debt can potentially enhance high-quality economic development, yet its effects and risks diverge substantially under the interplay of scale economies and diseconomies. Against the backdrop of the 20th CPC Central Committee's Third Plenary Session, which emphasized coordinated development-security integration and local debt risk resolution, this study investigates the debt-development nexus through the lens of dual-scale economies in explicit/implicit local government debt. We innovatively incorporate resource allocation efficiency and investment levels as mediating factors. Empirical results demonstrate the following: (1) An inverted U-shaped relationship between local debt scale and economic development quality during two debt rectification periods, with implicit debt exhibiting a more pronounced curvilinear pattern; (2) Both resource allocation efficiency and investment levels significantly moderate the scale economies of explicit/implicit debt, yet paradoxically constrain development quality. Key obstacles include short-term adjustment costs, income disparity, and innovation suppression. Notably, while government debt currently operates within scale economies, implicit debt possesses greater borrowing capacity than explicit debt. Debt-driven economies of scale exhibit significant regional heterogeneity. In coastal areas, these effects are more sustainable, whereas in inland areas it is relatively weak. Policy implications suggest the following: (1) Recognizing debt's nonlinear developmental impacts; (2) Optimizing resource allocation to improve investment quality; (3) Clarifying central-local fiscal responsibility demarcation; (4) A regionally differentiated collaborative strategy is needed for coordinating debt, investment, and resource allocation.
Keywords: 330; economies of scale; government borrowing; high-quality development; investment level; resource allocation efficiency